Pre-treatment With Fasudil Prevents Neomycin-Induced Hair Cell Damage by Reducing the Accumulation of Reactive Oxygen Species - Zhang, Yanqiu; Li, Wei; He, Zuhong; Wang, Yunfeng; Shao, Buwei; Cheng, Cheng; Zhang, Shasha; Tang, Mingliang; Qian, Xiaoyun; Kong, Weijia; Wang, Hui; Chai, Renjie; et al. (Frontiers in Molecular Neuroscience, 2019)
Ototoxic drug-induced hair cell (HC) damage is one of the main causes of sensorineural hearing loss, which is one of the most common sensory disorders in humans. Aminoglycoside antibiotics are common ototoxic drugs, and these can cause the accumulation of intracellular oxygen free radicals and lead to apoptosis in HCs. Fasudil is a Rho kinase inhibitor and vasodilator that has been widely used in the clinic and has been shown to have neuroprotective effects. However, the possible application of fasudil in protecting against aminoglycoside-induced HC loss and hearing loss has not been investigated. In this study, we investigated the ability of fasudil to protect against neomycin-induced HC loss both in vitro and in vivo. We found that fasudil significantly reduced the HC loss in cochlear whole-organ explant cultures and reduced the cell death of auditory HEI-OC1 cells after neomycin exposure in vitro. Moreover, we found that fasudil significantly prevented the HC loss and hearing loss of mice in the in vivo neomycin damage model. Furthermore, we found that fasudil could significantly inhibit the Rho signaling pathway in the auditory HEI-OC1 cells after neomycin exposure, thus further reducing the neomycin-induced accumulation of reactive oxygen species and subsequent apoptosis in HEI-OC1 cells. This study suggests that fasudil might contribute to the increased viability of HCs after neomycin exposure by inhibition of the Rho signaling pathway and suggests a new therapeutic target for the prevention of aminoglycoside-induced HC loss and hearing loss.